Strengthening Religious Character Through the Integration of Islamic Values in Learning - Millah Kamelia; Hanif Faddillah; Ayu Ida Mutiya; Irfan Pratama; Ahmad Jamin; Oki Mitra (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2026)
This study aims to analyze the strengthening of students’ religious character through the integration of Islamic values in sixth-grade Natural and Social Sciences learning at SDIT Darunnajah. The study was conducted based on the increasing need for integrative learning that combines scientific knowledge with spiritual and moral values to address the dichotomy between religious and general education. This research employed a qualitative approach using a case study design. Data were collected through observations, interviews, and documentation, while data analysis applied the interactive model consisting of data reduction, data display, and conclusion drawing. The findings revealed that the integration of Islamic values was systematically implemented through the stages of planning, implementation, and reflection. Islamic values were integrated by connecting Natural and Social Sciences materials with faith values, Qur’anic verses, hadiths, and natural phenomena as signs of Allah’s greatness. The integrated values included tauhid, gratitude, responsibility, honesty, humility, and enthusiasm for seeking knowledge. The integration process contributed positively to strengthening students’ religious character, as reflected in increased spiritual awareness, gratitude, responsibility, and religious behavior in daily life. Therefore, integrative Natural and Social Sciences learning based on Islamic values is effective in developing students who are intellectually competent while possessing strong religious character and spiritual awareness.